Leveraging Language: Preliminary evidence from a language-based intervention at the University of Cape Town - Whitelaw, Emma; Dowling, Tessa; Filby, Samantha (Critical Studies in Teaching and Learning, 2023)
This paper assesses the effectiveness of essay tutorials offered to first-year economics students at the UCT (University of Cape Town) in their first language (L1). All students in the study are first-language speakers of an African language. Firstly, using propensity score matching, we econometrically assess the impact of these tutorials on students’ essay marks. Although our sample size is small [n=220], our findings provide preliminary evidence of a positive impact of the intervention on a student’s final essay mark. The results show that the average gain for students who attended an essay tutorial in their L1 was 4.85%, with this result being statistically significant at the 10% significance level. Secondly, students’ perceptions of the tutorials’ effectiveness, as documented by online evaluations and focus groups, are examined. These findings suggest that allowing for unmediated L1 use in tertiary education classrooms can foster inclusivity and promote participation in otherwise largely monolingual spaces.